1984
DOI: 10.1038/307468a0
|View full text |Cite
|
Sign up to set email alerts
|

K channels in T lymphocytes: a patch clamp study using monoclonal antibody adhesion

Abstract: Ionic fluxes are thought to be involved in mediating the proliferation of peripheral blood lymphocytes (PBLs) in response to mitogenic substances. Among the earliest events occurring after the addition of mitogen to cultured lymphocytes are changes in rates of cation transport. We were interested, therefore, in the possible role of ion channels in mediating the lymphocyte proliferative response. The development of patch clamp techniques by Neher and colleagues has made it possible to study membrane conductance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
206
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(215 citation statements)
references
References 22 publications
9
206
0
Order By: Relevance
“…For data acquisition and analysis the pClamp10 software package (Molecular Devices, Sunnyvale, CA) were used. CD4 + T lymphocytes were selected for current recording by incubation with mouse anti-human CD4 antibodies (0.5 μg/10 6 cells, AMAC, Westbrook), followed by selective adhesion to petri dishes coated with goat anti-mouse IgG antibody (Biosource, Camarilo, CA), as described previously [39]. Standard whole-cell patch clamp techniques were used, as described previously [28].…”
Section: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…For data acquisition and analysis the pClamp10 software package (Molecular Devices, Sunnyvale, CA) were used. CD4 + T lymphocytes were selected for current recording by incubation with mouse anti-human CD4 antibodies (0.5 μg/10 6 cells, AMAC, Westbrook), followed by selective adhesion to petri dishes coated with goat anti-mouse IgG antibody (Biosource, Camarilo, CA), as described previously [39]. Standard whole-cell patch clamp techniques were used, as described previously [28].…”
Section: Electrophysiologymentioning
confidence: 99%
“…S5 and S6 segments with the pore loop between them form the pore domain (PD) of the channel which includes the ion conducting pore, whereas S1-S4 and the positively charged amino acids in S4 make up the voltage-sensing domain (VSD). Kv1.3, which belongs to the Shaker subfamily of Kv channels, is the predominant voltage-gated K + channel of human T lymphocytes [18,39].The main function of Kv1.3 channels during T cell activation is the maintenance of a permissive membrane potential (approximately equal to −50 mV) required for appropriate extracellular Ca 2+ entry and proper Ca 2+ signaling. By the use of Kv1.3-selective antagonists, lymphocyte proliferation and IL-2 production can be inhibited [14,47].…”
Section: Introductionmentioning
confidence: 99%
“…They remained in tissue culture for -I wk following initial harvesting and were used for electrophysiological experiments throughout the culture period. Experiments were performed on cells rounded in shape and estimated at [20][21][22][23][24][25][26][27][28][29][30] Am in diameter. All experiments were carried out at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that inhibition of Kv1.3 in lymphocytes 26,27 is immuno-suppressive 28 motivated us to test Sa SMase C against human Kv1.3. We found that Sa SMase C eliminates well over half of the ionic current of Kv1.3 and of the gating current of its non-conducting W384F mutant 29 (Fig.…”
mentioning
confidence: 99%